Transformasi Digital dalam Mendorong Ekonomi Berkelanjutan UMKM Melalui Aplikasi Buku Warung - Nurjanah, Rina; Tikaromah, Oom; Fauziah, Ela; Afganis, Laela Nabila; Andriyani, Meli (LPPM UNIVERSITAS NAHDLATUL WATHAN MATARAM, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a crucial role in the Indonesian economy, but many struggle with financial recording due to operational busyness, time constraints, and a lack of understanding. Inaccurate and manual financial records often lead to less effective and efficient business decisions, hindering MSMEs' ability to maximize profits. Therefore, this community service activity aimed to help MSMEs in the Bekasi Regency area prepare systematic and accurate financial reports. The methodology consisted of three stages: planning (preparation and observation), implementation (training), and monitoring and evaluation. The core activity involved training and assistance in digital financial recording using the Buku Warung application, which serves as a financial, payment, and bookkeeping service for MSMEs. The results indicate that partners successfully adapted to digital transformation through the application, as evidenced by its use in daily transactions. The application helped overcome their primary bookkeeping issues, allowing partners to prepare financial reports more independently. The activity's key implication is the focus on Digital Transformation and Improving MSME Financial Competence to support business sustainability. It successfully transitioned MSMEs from error-prone manual records to a digital system, resulting in more systematic and accurate financial reporting.